2012
DOI: 10.1108/13287261211221137
|View full text |Cite
|
Sign up to set email alerts
|

Soft skills requirements in software development jobs: a cross‐cultural empirical study

Abstract: Different parts of the world have different cultures and culture has an impact on the way people perceive, plan and execute any assignment. The success and failure stories of software projects reveal that human factors are one of the significantly important issues. Psychological theories assert that people have different personality traits and these personality traits are pigeonholed by soft skills or emotional intelligence.Most of the studies carried out on human factor in software engineering concentrate pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 46 publications
3
48
0
3
Order By: Relevance
“…One of the difficulties in creating effective OLEs is student isolation, which is said to invoke an individual-centric model of learning that encourages discrete study rather than teamwork (Haythornthwaite, Kazmer, Robins, & Shoemaker, 2000;Morgan & Tam, 1999). Despite this, employers still insist that a key learning objective of ICT graduates is the ability to work in team environments as this mirrors work force requirements (Ahmed et al, 2012;Australian Workforce and Productivity Agency, 2013). Due to this need, group exercises and projects have become an important component of higher education (Blackman, 2012;Friedman, Cox, & Maher, 2008;Myers, Monypenny, & Trevathan, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the difficulties in creating effective OLEs is student isolation, which is said to invoke an individual-centric model of learning that encourages discrete study rather than teamwork (Haythornthwaite, Kazmer, Robins, & Shoemaker, 2000;Morgan & Tam, 1999). Despite this, employers still insist that a key learning objective of ICT graduates is the ability to work in team environments as this mirrors work force requirements (Ahmed et al, 2012;Australian Workforce and Productivity Agency, 2013). Due to this need, group exercises and projects have become an important component of higher education (Blackman, 2012;Friedman, Cox, & Maher, 2008;Myers, Monypenny, & Trevathan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Soft skills increase the employability of graduates who can demonstrate effective communication skills with clients and colleagues (McMurtrey, Downey, Zeltmann, & Friedman, 2008). Some researchers contend that these skills are often overlooked within the tertiary level curriculum, particularly with the recent shift towards online delivery (Ahmed, Capretz, Bouktif, & Campbell, 2012;Chan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies showed changing skill requirements over time with increased emphasis on soft skills rather than job or profession-specific skills (Hawkins et al, 2000;Quinn & Rochford, 2013;Cramer & Tenzek, 2014). Monitoring of market trends to define current skill requirements was well supported although cultural and other contextual differences were acknowledged, (Cullen 2003;Den Hartog et al, 2007;Ahmed, Capritz, Bouktif, & Campbell 2012;Reeves & Hahn, 2012;Kuokkanen et al, 2013;Ahsan et al, 2013). In fact one third (13) of the studies specifically recommended that HEI should use their findings for academic advising, updating curriculum and to help new graduates align with skill requirements of industry.…”
Section: Value Of the Researchmentioning
confidence: 99%
“…One study revealed a poor match between curriculum and professional competency lists (France 2010). Three studies saw value in current employees, employers, human resources managers or graduates using their findings (Ahsan et al, 2012;Ahmed et al, 2012;Messum et al, 2011). The importance of work experience was also confirmed and taken to support the importance of work integrated learning and industry placements, (Messum et al, 2011).…”
Section: Value Of the Researchmentioning
confidence: 99%
“…cc Engineering software revolves around methodologies establishing (more or less) well-defined processes to develop a product. 21 However, because people execute these processes, no matter how good they are, the ultimate success lies in how the processes are being executed especially when people interact. The successful implementation of any process methodology ultimately depends on how employees perceive that methodology.…”
mentioning
confidence: 99%